Co-occurrence of Point Mutations in the Voltage-Gated Sodium Channel of Pyrethroid-Resistant Aedes aegypti Populations in Myanmar - Kawada, Hitoshi; Oo, Sai Zaw Min; Thaung, Sein; Kawashima, Emiko; Maung, Yan Naung Maung; Thu, Hlaing Myat; Thant, Kyaw Zin; Minakawa, Noboru (PLOS Neglected Tropical Diseases, 2014)
Author Summary The use of pyrethroids with high killing activity has accelerated the development of pyrethroid resistance in vector mosquitoes. The knockdown resistance (kdr) allele contains a single amino acid substitution in the voltage-gated sodium channel and is one of the main causative factors of pyrethroid resistance in insects. We investigated the distribution of the kdr gene in Aedes aegypti larvae collected from used tires in Yangon City, Myanmar. We detected three patterns of co-occurrence of point mutations, namely, V1016G/S989P with wide distribution, and small number of V1016G/F1534C and V1016G/F1534C/S989P, both of which were first found in the field collected Ae. aegypti population. The use of pyrethroids and/or DDT for malaria control is thought to be one of the main causes of pyrethroid resistance in Aedes aegypti. Insecticide treatment for malaria vector control seems to have been intensively conducted in the interior and along the periphery of human habitation areas, where the breeding and resting sites of Aedes aegypti are located.